Critical Care Study Guide Text and Review - Criner, Gerard J.; Barnette, Rodger E.; D'Alonzo, Gilbert E. (Springer New York : Imprint: Springer, 2010)
The second edition of this best-selling study guide and text covers all aspects of critical care medicine. Written by a diverse group of physicians and health care personnel, it is of interest to all professionals who care for the ICU patient. The unique format includes key points highlighted in the margins for quick reference and self-assessment questions and answers at the end of each chapter. The text is supported by case studies, tables, and numerous illustrations that detail key procedures. The new edition has been revised substantially to reflect the most current research and guidelines, and new chapters have been added to make this the most practical and comprehensive study guide and text available today.